+0  
 
+3
94
1
avatar+40 

What is the sum of all real values of x that satisfy the equation (x-3)(x^2+4x+4)=x-3?

 Nov 26, 2020
 #1
avatar+116126 
+2

(x - 3) ( x^2 + 4x + 4)   = (x - 3)

 

(x - 3) ( x + 2)^2  = (x - 3)

 

( x  - 3) )x + 2)^2  - (x - 3)   = 0

 

(x -3)  [ (x + 2)^2   - 1 ) ]  =  0           

 

( x - 3)  [ ( (x + 2) + 1  )  ( (x + 2)  - 1) ]   = 0

 

(x - 3)  [ x + 3)  ( x + 1) ]  =  0       set each factor  to 0  and solve for  x

 

x - 3  = 0       x + 3   = 0         x  + 1   = 0

 

x = 3             x  = -3                 x   = -1

 

 

cool cool cool

 Nov 26, 2020

69 Online Users